Isolation and molecular characterization of virulent and avirulent strains of Vibrio alginolyticus - Abdul Razak, Rashidah (2013)
Vibriosis caused by Vibrio alginolyticus has been recognised as serious disease problem. Although V. alginolyticus were reported to be pathogen but it also been used to formulate probiotics used in shrimp aquaculture. Therefore, indigenous marine strains of V. alginolyticus were isolated and selected to study their virulence in shrimp postlarvae. The bacteria were isolated from 20 water and 20 sediment samples collected from natural environment and shrimp ponds in Selangor and Sabah, Malaysia. From the total of 79 isolates which formed yellow colonies on TCBS agar plates, 15 were identified as V. alginolyticus using gyrB gene based PCR and showed 94 to 100% similarity to the partial sequence of V. alginolyticus 16S rRNA gene. From the 15 isolates, only six were chosen for pathogenicity study which consisted of one beta, three alpha and two gamma hemolysis type of strains. After 24 hours of incubation in TSB with shaking at 30 °C, these isolates showed different OD readings and the highest was 1.7554 ± 0.0031 with cell number of 4.72 X 109 ± 2.74 X 108 CFU.mL-1 indicating that V. alginolyticus M2 showed the best growth rate in TSB with 1.5% NaCl compared to other isolate In the pathogenicity test, three treatments consisting of different concentrations of bacteria (103, 105 and 107 CFU.mL-1) and one control group contained physiological saline were performed on shrimp postlarvae. There was a significant difference (p<0.05) in the mortality rate of the postlarvae between the three treatments used and the tests revealed that the mortality rate of the shrimp postlarvae increased with duration of exposure. The highest mortality was noted in V. alginolyticus M13 tanks at concentration of 1.28 X 107 CFU.mL-1 where the average mortality was 98.4 ± 1.7%. Furthermore, the LD50 study showed that the lowest value was 4.33 X 104 CFU.mL-1 for V. alginolyticus M13 and the highest value was 8.11 X 109 CFU.mL-1 for V. alginolyticus M2 indicating the isolates varied in virulence. The isolates were characterized as highly virulent were V. alginolyticus M13 and S7, weakly virulent were V. alginolyticus G3 and S48 and avirulent were V.alginolyticus M2 and G34. In order to distinguish between virulent and avirulent strains, four primers were used in RAPD analysis. From this, we deduced that only one primer (GTG5 primer) was suitable to characterise six strains of V. alginolyticus. Using the fingerprint patterns obtained, a dendrogram was constructed; these strains were divided into two main clusters, two subclusters and two different groups. The homogeneity between the strains ranged from 11.8 to 80.0%. The genetic distances between the virulent strains were 37.5% and 23.5% for avirulent strains which classified them into two distinct clusters and subclusters respectively. The weakly virulent strains showed high homogeneity as their genetic similarity was 62.5%. In addition, the strains isolated from the same source also showed genetic variation. For example, strains M2 and M13, S7 and S48 isolated from same shrimp farm showed only 41.7% and 53.3% homogeneity respectively. The results showed that isolates from the same source and having same virulence degree varied in their genetic profiles.